Regulation of Human Osteoclast Development by Dendritic Cell-Specific Transmembrane Protein (DC-STAMP) - Chiu, Ya-Hui (2012)
Osteoclasts (OC) are bone-resorbing, multinucleated cells that are generated via fusion of OC precursors (OCP). The frequency of OCP is elevated in patients with erosive inflammatory arthritis and metabolic bone diseases. Although many cytokines and cell surface receptors are known to participate in osteoclastogenesis, the molecular mechanisms underlying the regulation of this cellular transformation are poorly understood. Herein, we focused our studies on the dendritic cell-specific transmembrane protein (DC-STAMP), a seven-pass-transmembrane receptor-like protein known to be essential for cell-to-cell fusion during osteoclastogenesis. We identified an immunoreceptor tyrosine-based inhibitory motif (ITIM) in the cytoplasmic tail of DC-STAMP, and developed an anti-DC-STAMP monoclonal antibody 1A2 that detected DC-STAMP expression on human tumor giant cells, blocked OC formation in vitro, and distinguished four patterns of human PBMC with a positive correlation to OC potential. In freshly isolated monocytes, DC-STAMP(high) cells produced a higher number of OC in culture than DC-STAMP(low) cells and the surface expression of DC-STAMP gradually declined during osteoclastogenesis. Importantly, we showed that DC-STAMP is phosphorylated on its tyrosine residues and physically interacts with SHP-1 and CD16, an SH2-domain-containing tyrosine phosphatase and an ITAM-associated protein, respectively. Taken together, these data show that DC-STAMP is a potential OCP biomarker in inflammatory arthritis. Moreover, in addition to its effect on cell fusion, DC-STAMP dynamically regulates cell signaling during osteoclastogenesis.